The Role of Financial Institutions in Financial Intermediation and Its Impact on Economic Growth - Khusnul Khatimah; Dian Anggraeni; Muchriana Muchran; Rum (Pustaka Digital Indonesia, 2026)
Financial institutions play a crucial role in modern economic systems by facilitating financial intermediation, which involves mobilizing funds from surplus units and allocating them to deficit units. This process enhances capital allocation efficiency, supports investment activities, and contributes to sustainable economic growth. This study aims to examine the role of financial institutions in financial intermediation and analyze its impact on economic growth. The research employs a qualitative approach using a systematic literature review (SLR) method, synthesizing recent empirical and theoretical studies published between 2021 and 2026, complemented by seminal works to strengthen the conceptual framework. The findings reveal that financial institutions, particularly banks, remain the dominant actors in financial intermediation and play a significant role in promoting economic growth. The effectiveness of financial intermediation is influenced by several key factors, including financial inclusion, regulatory quality, institutional governance, and technological innovation. In addition, the emergence of financial technology (fintech) has transformed traditional intermediation processes by improving efficiency and expanding access to financial services. However, excessive credit expansion and weak regulatory frameworks may lead to financial instability, indicating a nonlinear relationship between financial intermediation and economic growth. This study contributes to the literature by providing an integrative and up-to-date synthesis of the finance–growth nexus and offers policy implications for strengthening financial systems to achieve inclusive and sustainable economic development.